Henry Smith Kelley, Laws Applicable to and Governing the City of Saint Joseph, Mo., As a City of the Second Class, Contained in the Revised Statutes of 1879, and Subsequent Legislative Enactments; Also the General Ordinances Now in Force, Revised and Made to Conform to the Laws Governing Such Cities Page 192, Image 222 (1888) § 3 - (:unkn) unknown (General Publisher, 1888)
No person shall carry on or take part in carrying on, any pistol gallery or shooting gallery, without a license therefor from said city; and the charge for such license shall be five dollars per month.
--
Keywords: SHOOTING RANGES OR GALLERIES